The importance of environmental education in the implementation of reverse logistics retail - Dias, Karin Tonelli Siveira [UNESP]; Junior, Sergio Silva Braga [UNESP] (My University, 2015)
The adoption of environmental practices is growing in the retail supermarket. Thus, demonstrate the environmental advantages and the importance of environmental education in the implementation of reverse logistics practices in the retail supermarket was the objective of this research. In order to achieve a field research with participatory observation was carried out for 6 months at a supermarket in the state of São Paulo/Brazil to follow environmental education incorporated into daily life and their results generated by each department. Using the method Wuppertal, was quantified the volume of waste which ceases to be generated in each department after implementation. By participant observation, a new routine was noted part of daily life and a new attitude that has generated benefits in the workplace and contributing to the sustainability of the business by reducing the disposal of influencers materials on global warming and the depletion of the ozone layer.
Keywords: Education; Environmental